Development and validation of the Sorting non-trauMatIc adoLescent knEe pain (SMILE) tool - a development and initial validation study - Clara Guldhammer; Sinead Holden; Marina Elmelund Sørensen; Jens Lykkegaard Olesen; Martin Bach Jensen; Michael Skovdal Rathleff (BMC, 2021)
Abstract Background Despite the commonality of adolescent knee pain, there are no tools to support medical doctors to correctly diagnose knee pain. This study aimed to develop and evaluate a support tool for diagnosing the most common types of non-traumatic adolescent knee pain. Method A systematic search on Medline identified the literature on clinical tests and diagnoses of adolescent knee pain. The search was supplemented by textbooks and transformed into a diagnostic flowchart based on onset, symptoms, and pain localisation. This tool was revised based on feedback from general practitioners and experts in sports medicine. The tool was evaluated on two separate days with blinded assessors. Overall, 27 participants (aged 10-17 years) with non-traumatic knee pain were included. All participants were diagnosed by medical doctors or medical students, without and with the use of the tool. Diagnoses were compared to a gold standard (expert clinician). An interview to inform optimisations of the tool was performed with the assessors. Percentage agreement with the gold standard, and Kappa statistic for interrater reliability were calculated. Results The final tool improved diagnostic agreement with the gold standard from 22.7% (95% CI 10.3-35.1) to 77.3% (95% CI 64.9-89.7). Inter-rater reliability increased from poor agreement k = − 0.04 (95% CI, − 0.12-0.04 ) to moderate agreement k = 0.56 (95% CI, 0.40-0.72). Conclusion This simple diagnostic tool is quick to use and may assist doctors in diagnosing non-traumatic knee pain in adolescents.